Peramalan Harga Saham PT Bank Central Asia Tbk (BBCA) Menggunakan Metode SARIMA Periode 2019-2024 - Nuha, Alvin Vikrun; Herawati, Sri (Universitas Muhammadiyah Ponorogo, 2025)
The Indonesian capital market has shown significant development with the number of investors reaching 10.32 million SID as of December 2023. However, stock investment still faces challenges in the form of unpredictable price fluctuations. This study aims to forecast the stock price of PT Bank Central Asia Tbk (BBCA) using the SARIMA method for the 2019-2024 period. The data used is sourced from Yahoo Finance spanning from January 2019 to January 2024. The analysis results show that the SARIMA model ((1,0,0),(0,0,0,12)) can be used to forecast BBCA stock prices. Based on the forecasting results for the next 30 days, BBCA's stock price shows an upward trend. This study also indicates that stock price movements are not only influenced by time factors but also other factors, so it is recommended for future research to use Multivariate Time Series analysis.